PENGARUH TINGKAT SUKU BUNGA, INFLASI DAN NILAI TUKAR TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Suriyani, Ni Kadek; Sudiartha, Gede Mertha (E-Jurnal Manajemen, 2018)
Return is a reward for investor bravery in taking risks on the investment it does. Recurn can motivate and attract investors to invest. The rate of return earned by investors is influenced by microeconomic factors and macroeconomic factors. In this research, factors that influence stock return use macroeconomic factors, ie, interest rate, inflation, and exchange rate. This study aims to obtain empirical evidence on the influence of interest rates, inflation and exchange rates on stock returns. This research was conducted on property and real estate companies in Indonesia Stock Exchange. The population used is all property and real estate companies listed on the IDX period 2013-2016. Sample determination method used is to use saturated samples. Data analysis used is multiple linear regression test. Based on the results of this study found that the interest rate has a positive and insignificant effect on stock returns. Inflation has negative and insignificant effect on stock return, while exchange rate has negative and significant effect on stock return. Keywords : i nterest rate, inflation, exchange rate, and stock return.